RELEVANSI ALIRAN PENDIDIKAN PROGRESIVISME DALAM TRANSFORMASI PEMBELAJARAN DI ERA DIGITAL DAN GLOBALISASI - Khikmah, Risalatul; Marfu'ah, Jihan Aulia; Aulianisa, Fadhillah; Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The era of digitalization and globalization has brought about fundamental changes in the education system. This demands a shift from conventional teacher-centered teaching methods to a more flexible, student-centered model. This article aims to examine the suitability of John Dewey's progressivism philosophy as a theoretical basis for transforming the teaching and learning process in the contemporary era. This research method utilizes a library study by conducting a literature review over the past five years. This study seeks to investigate the potential integration of the principles of learning by doing and the acquisition of factual experience with the use of digital technology. Data analysis indicates that progressivism has high relevance when implemented through the implementation of blended learning based on the TPACK framework, the Merdeka Committee, and efforts to strengthen 21st-century competencies, including critical thinking and collaboration skills. Despite obstacles such as infrastructure disparities and limited digital literacy among educators, progressivism provides a strong framework for realizing an inclusive, democratic, and future-oriented education system.